A homozygous missense variant in DND1 causes non-obstructive azoospermia in humans - Xie, Xuefeng; Khan, Mazhar; Zubair, Muhammad; Khan, Abbas; Khan, Ranjha; Zhou, Jianteng; Zhang, Yuanwei; Said, Muzafar; Khan, Sher Ali; Zaman, Qamar; Murtaza, Ghulam; Khan, Muzamil Ahmad; et al. (Frontiers in Genetics, 2022)
Non-obstructive azoospermia (NOA) is a severe factor of male infertility; it affects approximately 1% of the global male population and accounts for 40% of male infertility cases. However, the majority of NOA cases remain idiopathic. This is the first study using whole-exome sequencing (WES) to identify a novel missense mutation in the DND1 gene (c.212A>C, p.E71A) from a Pakistani family, that includes three males with NOA. This mutation is predicted to cause DND1 protein misfolding and weaken the DND1 interaction with NANOS2, a significant regulator in primordial germ cell development. Our study identified a Dnd1 pathogenic mutation in NOA patients and highlighted its critical role in male fertility in humans.